The Effect of Project Based Learning (PjBL) - STEM in Improving Students' Science Literacy Skills on Topic of Alternative Energy - Berliana, Dinda Rizky; Suwarma, Irma Rahma; Novia , Hera (Department of Physics Education, Universitas Mataram, 2024)
Science literacy skills are one of the abilities in understanding scientific knowledge to solve problems in everyday life. However, science literacy in Indonesia is still classified as low. So that in the independent curriculum currently used in education, science literacy is one of the competencies that is very important and also needed by Pancasila students. The purpose of this study is to analyze the improvement of science literacy skills as a result of PjBL - STEM learning in class X in one of Bandung State High School on alternative energy material. The sampling consisted of 32 students and the sampling technique was taken using convenience sampling technique. Data collection used is by formative test description of science literacy skills. The test instruments used were 2 questions identifying scientific issues, 2 questions explaining scientific evidence, and 3 questions explaining scientific evidence. The method used in this research is pre-experiment method using one group pre-test - post-test research design. The data that has been obtained is analyzed using the N-Gain value and effect size. The results showed that the value of students' science literacy skills increased with an average post-test score of 83.16 and the overall N-Gain value obtained was 0.57 and included in the moderate category, then the increase in students' science literacy in each indicator, namely in identifying problem issues, explaining scientific phenomena, and explaining scientific evidence has a moderate category. However, of the three indicators, the indicator of identifying scientific issues has the smallest N-Gain of 0.51. The calculation of the effect size value is carried out to determine how much influence learning using the PjBL-STEM model has in improving science literacy skills, so that in the research that has been done it is found that the effect size is 3.23 and is included in the